Penerapan Data Mining Untuk Memprediksi Jumlah Data Pasien Di Puskesmas Haekesak Menggunakan Metode ARIMA - Ermelinda Novita De Jesus; Anief Fauzan Rozi (Journal of Information System and Artificial Intelligence, 2021)
ABSTRACT The purpose of this study was to determine the Arima method equation model, to find out the resultsof the analysis to predict the number of patients in the haekesak health center using Minitab tools. and knowingthe results of predicting the number of patients treated at the Hasekesak health center from 1 January to 10February and the method used in this study was the ARIMA method. The results of the prediction of the totalnumber of patients who will come to the Haekesak Health Center using the ARIMA method, this analysis endswith the number of patients who will come on the 26th-35th day where the total number of patients does notincrease or decrease significantly so that the puskesmas does not need to increase their mental health. or theaddition of excessive drug stock.Keywords: Forecasting, ARIMA, Disease